"Diversity is a corporate plan": racialized equity labor among university employees. Issue 6 (26th April 2023) - Hamilton, Laura T.; Nielsen, Kelly; Lerma, Veronica
ABSTRACT: Drawing on ninety-four interviews with university employees at two four-year publics, we identify elements of the "racialized equity labor", or efforts to challenge racial inequities in the university environment, primarily undertaken by employees of color. We argue that the amount and intensity of racialized equity labor is related to organizational logics of race, or cultural values and beliefs about race that people use to organize their activities in the university. "Diversity" logics, focusing on individual differences in experiences, values, and worldviews, are associated with identity-focused infrastructure and create greater need for racialized equity labor. In contrast, "equity" logics focus on the structural changes needed to address race as a system of oppression and are instantiated in institutionalized infrastructure that alleviates and transforms racialized equity labor. We conclude that diversity logics are profoundly limiting for addressing racial inequities in academia.